High hydrostatic pressure blanching of baby spinach (Spinacia oleracea L.) - Finten, Gabriel (2016)
Given the high susceptibility of baby spinach leaves to thermal processing, the use of high hydrostatic pressure (HHP) is explored as a non-thermal blanching method. The effects of HHP were compared with thermal blanching by following residual activity of polyphenol oxidases and peroxidases, colour retention, chlorophyll and carotenoids content, antioxidant capacity and total polyphenols content. Spinach subjected to 700 MPa at 20 °C for 15 min represented the best treatment among the conditions studied due to its balanced effect on target enzymes and quality indices. The latter treatment reduced enzyme activities of polyphenol oxidases and peroxidases by 86.4 and 76.7%, respectively. Furthermore, leaves did not present changes in colour and an increase by 13.6% and 15.6% was found in chlorophyll and carotenoids content, respectively; regarding phytochemical compounds, retentions of 28.2% of antioxidant capacity and 77.1% of polyphenols content were found. Results demonstrated that HHP (700 MPa) at room temperature, when compared with thermal treatments, presented better retention of polyphenols, not significantly different chlorophyll and carotenoids content and no perceptible differences in the instrumental colour evaluated through δE value; therefore, it can be considered a realistic practical alternative to the widely used thermal blanching.